Tramadol in Oral Surgery – A Literature Review (Indian Journal of Forensic Medicine & Toxicology, 2020)
Elimination of pain is one of the most important duties of a doctor. A surgeon has to come across morenumber of cases where management of pain becomes a handful. Thus proper use of analgesics both systemicand local are an integral part of any successful surgery. For decades NSAIDs has been the go to drug formanagement of pain and administering anaelgesia. But recent pharmacological advancements have openedup a new way of administering anaelgesia in the form of synthetic opiods. This review article aims at findingout the efficacy of local administration of TRAMADOL in maxillofacial surgeries.
Keywords: Tramadol, Opiods In Oral Surgery